On the Reversed Images of the Evangelists in Old Russian Manuscripts - Smirnova, Engelina S. (Actual Problems of Theory and History of Art, 2019)
In the miniatures of Gospels manuscripts belonging to the Byzantine world the four evangelists writing their texts are sometimes represented on the left side of the book opening in pairs turning to each other. One of such examples is found in the miniatures of the Gospels Chlud. 30 from the State Historical Museum (Novgorod, 1330–1340s). These miniatures repeat in a somewhat simplified form the images on the bronze Royal Doors from Novgorod dating to the same period and now kept in the State Russian Museum, and on the fragments from other similar doors now divided between the State Russian Museum, the State Hermitage and the Louvre. Our survey of illuminated Gospels shows that such “reversed”images of the evangelists existed in Byzantium (e.g. in the 10th-century Gospels Stavronikita 43 from Mount Athos), but more often in Rus, from the 12th century on (e.g. Dobrilo Gospels of 1164 in the Russian State Library, f. 256 Rumyants., no. 103). There are some other examples dating from the 14th or early 15th century. Analysis of these manuscripts’ structure shows that the use of such iconography was not connected with the desire to spare the parchment. We suggest that miniatures with the “reversed” evangelists rather reproduce similar images in church decoration, for example, the wall paintings in the pendatives and the images of the evangelists on the iconostasis doors. Similar iconography is also encountered on the precious revetments of the Gospels books.
Keywords: manuscripts; miniatures; evangelists; iconostasis doors; pendatives; Gospels books revetments; “reversed” compositions